Implementation Factors and Their Influence on Student Mathematics Outcomes. Issue 1 (7th January 2023) - Brafford, Tasia; Harn, Beth; Clarke, Ben; Doabler, Christian T.; Kosty, Derek; Scalise, Kathleen
Abstract: Assessing implementation allows for a better understanding of an intervention's effects and the mechanisms that influence its impact. Two main areas of implementation are (a) the quality with which an intervention is delivered and (b) instructors' adherence to the programmed intervention. The current study used data from a kindergarten mathematics intervention program to (a) examine if and how treatment adherence was associated with implementation quality and (b) explore implementation measures' relation to student mathematics outcomes. Results indicated high implementation scores across time for both adherence and quality. Neither treatment adherence nor implementation quality was found to relate to a general outcome measure of student mathematics achievement; however, both were similarly related to the curricular‐aligned measure.